Unusual Complications in Cocaine Stuffers: A Case Report - Hassan Al-Balushi; Andres Guzman-Soto; Kyle Suen; Al Yaqdhan Al Atbi; Ziad Kazzi; Jonathan de Olano; Todd Taylor (Clinical Practice and Cases in Emergency Medicine)
Introduction: Body stuffing is defined as ingesting small quantities of drugs in poorly sealed packets, often to avoid repercussions from law enforcement. Cocaine is one of the drugs most commonly involved. Complications reported with stuffing include aspiration, esophageal obstruction, and fatal toxicity. Survival from mechanical airway obstruction due to drug stuffing has not been reported. Case Report: We present a case of a 32-year-old male who was a cocaine body stuffer, complicated by agitated delirium, cardiotoxicity, and airway obstruction requiring resuscitation, followed by a surgical tracheostomy to retrieve the obstructing cocaine bag. The patient’s hospital course was further complicated by rhabdomyolysis and acute kidney injury requiring dialysis. He was discharged in stable condition after a four-week hospital stay. Conclusion: This case highlights the severe risks of cocaine body stuffing, including airway obstruction and cocaine-induced arrhythmias. Endotracheal intubation in such cases warrants a careful airway assessment to mitigate the risks of obstructive complications.